THE USE OF SENTINEL-2A IMAGERY FOR MAPPING THE CONVERSION OF AGRICULTURAL LAND INTO DEVELOPED LAND USING THE OBIA METHOD IN BATANG ANAI DISTRICT 2017 AND 2022 - syahadani, meilani; Syarief, Azhari; Ramadhan, Risky; Fitriawan, Dedy (Remote Sensing Technology Study Program, 2024)
Indonesia is a developing country with a population growth rate of 1.38%. Due to the relatively strong population growth every year, this greatly affects land change. Therefore, the phenomenon of land use change emerged. In general, the rate of population growth correlates with the rate of land use change, which results in increased satisfaction of land-use needs such as settlements and public facilities. This study aims to determine the Change in Land Cover resulting from the Change of Agricultural Land Function into developed land and where the direction of changing agricultural land to developed land in Batang Anai District. This study uses a quantitative approach by utilizing Remote Sensing using Object-Based Classification (OBIA). Based on the interpretation results on Sentinel-2A images in 2017 and 2022, 8 land cover classes were found with an Overall Accuracy of 91% and a Kappa Index of 89.80%. Agricultural land in Batang Anai District has undergone land conversion into built-up land of 304.2 Ha or 8.70% of the agricultural land area in Batang Anai District with a total of 3499.16 Ha so that the remaining agricultural land area in 2022 is 3194.96 Ha. As a result of the land use change, there was a development of built-up land which was converted into housing development, public facilities and the Padang-Pekanbaru toll road leading from South to North.